Non-take up i det svenska välfärdssystemet: Om betydelsen av social position för kvinnors beslut kring mammografiscreening (Sociologisk Forskning, 2016)
Non-take up in the Swedish welfare system: On the impact of social position on women’s decision-making regarding mammography screeningCentral to a well-functioning and effective welfare system is that benefits reach the people to whom they are intended. By focusing on an example of so called non-take up – namely women’s decision not to attend mammography screening – this article discusses decision making in relation to living conditions, i.e. social position, and to the public health intentions of the welfare state. The main theoretical basis for the analysis is Rogers’ humanistic/existential theory. Qualitative semi-structured interviews were made with 18 women who had abstained from mammography screening. Their decision was described, analyzed and problematized focused on whether their living conditions, leading to a strong or weak social position, is of relevance to their decision to refrain from this health promoting examination. The women’s own experiences clearly showed how their social position was of great importance for how they explained their decision to abstain. Furthermore, social position affects how women handle different impact from living conditions, society’s expectations and personal experiences of mammography screening. This study makes visible the gap between public health intentions of the society and individual conditions.